Pharmacokinetic Characterization and Comparative Bioavailability of an Innovative Orodispersible Fixed-Dose Combination of Ivermectin and Albendazole: A Single Dose, Open Label, Sequence Randomized, Crossover Clinical Trial in Healthy Volunteers - Algorta, Jaime; Krolewiecki, Alejandro; Pinto, Filipe; Gold, Silvia; Muñoz, Jose (Frontiers in Pharmacology, 2022)
Soil-transmitted helminths are intestinal worm diseases transmitted through soil. Available treatments are albendazole and/or ivermectin. The co-administration of existing drugs is an appropriate strategy. A fixed-dose combination adds practical advantages mainly considering mass drug administration. The aim is to characterize the pharmacokinetics and to evaluate the comparative bioavailability of an innovative fixed-dose combination of ivermectin/albendazole 18/400 mg compared with the marketed references. Seventy-eight healthy volunteers were included in this laboratory-blinded, randomized, three-treatment, three-period crossover study. Each subject received a single dose of ivermectin/albendazole 18/400 mg (1 tablet); ivermectin 3 mg (6 tablets); and albendazole 400 mg (1 tablet). Serial blood samples for pharmacokinetic analysis were obtained pre-dose and up to 72 h post-dose. Plasma concentrations of ivermectin H2B1a, ivermectin H2B1b, albendazole and albendazole sulfoxide were analyzed by LC-MS/MS. Pharmacokinetic parameters were estimated by non-compartmental analysis and bioavailability compared through a bioequivalence analysis. Safety and tolerability were assessed throughout the study. Main pharmacokinetic parameters of the fixed combination were estimated for both, Ivermectin (Cmax (mean, Confidence Interval): 86.40 (30.42-39.23) ng/mL; AUC0-72 (mean, CI): 1040 (530-1678) ng·h/mL; tmax (median, min., max.); 4.50 (2.50-5.50)) and Albendazole Cmax (mean, CI): 22.27 (1.89-111.78) ng/mL; AUC0-72 (mean, CI): 94.65 (11.65-507.78) ng·h/mL; tmax (median, min., max.): 2.50 (1.00-12.00) h). The 90% confidence interval of geometric mean ratios demonstrated bioequivalence in the case of ivermectin (Cmax: 110.68 -120.49%; AUC0-72: 110.46 -119.60%) but not in the case of albendazole (Cmax: 53.10 – 70.34%; AUC0-72: 61.13 – 76.54%). The pharmacokinetic profile of a new fixed-dose combination of ivermectin and albendazole was characterized. The bioequivalence versus the reference ivermectin was demonstrated, though the bioequivalence versus albendazole was not shown. The three medications analyzed were well tolerated. The results allow the advance to the next phase of the clinical program to demonstrate efficacy and safety in patients affected by soil-transmitted helminths. EudraCT No: 2020-003438-19